Estudo de caso sobre o método construtivo de paredes de concreto moldadas "in loco" em casas populares no Município de Mossoró - RN - Fonseca, Amanda Fernandes Tomaz (Universidade Federal Rural do Semi-Árido, 2019)
The need for agility in the execution of public works has led the builders to seek more and more methods capable of rationalizing the costs of labor and time of service. The construction system of molded concrete walls "in loco" is an innovative method and, although little known in Brazil, it has been presented as a very effective alternative, mainly for constructions linked to the Federal Government program "Minha Casa, Minha Vida" which require agility and economy in production without compromising the quality and performance of the finished product. Thus, the objective of the work is to demonstrate the method and describe its processes, presenting the advantages and disadvantages that peer the system. The methodology used in the work was the case study of a horizontal residential condominium project with 152 houses executed with the concrete walls method molded in the place. A survey of the main pathologies presented in the structure of the concrete walls was carried out. Also, it was estimated a budget referring to the costs of walls for comparative with the system of conventional masonry with ceramic block, in addition to a schedule of execution. The results were satisfactory for the method, because with the comparison it was possible to obtain positive results both qualitatively and economically.
Monografia
Keywords: Paredes de concreto; Patologias; Fôrmas; Racionalização; Concrete walls; Pathologies; Forms; Rationalization; ENGENHARIAS::ENGENHARIA CIVIL